ESTIMATION OF EXTREME WAVE CONDITIONS IN THE SOUTHERN NHA TRANG BAY AREA - Mau, Le Dinh (Vietnam Journal of Marine Science and Technology, 2008)
This paper presents the distribution features of calculated maximum significant wave height in the Southern Nha Trang bay area corresponding to maximum wind speed of 50 years return periods. Wind data from 1976 to 2006 were taken from Nha Trang Meteorological Station. Weibull distrihution function was used to estimate maximum wind speed for different return periods. Dolphin and SWAN models were used to estimate wave characteristics in the offshore and nearshore regions, respectively. The studied results show that maximum wind speeds for 50 years return period were 27, 22, 15 and 17 m/s in NE, E, SE and S directions, respectively. The areas of Southern Tre Island including Nha Trang Port, Mieu, Mot, Tam and Mun islands were strongest affected by wave action from E and S directions with significant wave height of 2 - 4 m, and lesser affected by wave action from NE and SE directions with significant wave height of 2 m. The area between Mun Island to Noi and Ngoai Islands, and the coastline from Dong Ba to Cam Ranh Headlands were strongest affected by wave action from E and NE directions with significant wave height of 4 - 7 m, and lesser affected by wave action from SE and S directions with significant wave height of 2 - 3 m. Maximum wind field blown from SW direction (V = 19 m/s) was generated a relatively strong wave field in the studv area, especialy in the area around Mun and Mot Islands with significant wave height range from 1.5 to 2.0 m. In general, for maximum wind speed of 50 years return period the southern area of Nha Trang bay was strongest affected by wave action from E and NE directions.